Genome‐wide association analysis of serum alanine and aspartate aminotransferase, and the modifying effects of BMI in 388k European individuals. Issue 6 (29th June 2021) - Gao, Chuan; Marcketta, Anthony; Backman, Joshua D.; O'Dushlaine, Colm; Staples, Jeffrey; Ferreira, Manuel Allen Revez; Lotta, Luca A.; Overton, John D.; Reid, Jeffrey G.; Mirshahi, Tooraj; Regeneron Genetics Center; Geisinger Regeneron Discovehr Collaboration; et al.
Abstract: Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are biomarkers for liver health. Here we report the largest genome‐wide association analysis to date of serum ALT and AST levels in over 388k people of European ancestry from UK biobank and DiscovEHR. Eleven million imputed markers with a minor allele frequency (MAF) ≥ 0.5% were analyzed. Overall, 300 ALT and 336 AST independent genome‐wide significant associations were identified. Among them, 81 ALT and 61 AST associations are reported for the first time. Genome‐wide interaction study identified 9 ALT and 12 AST independent associations significantly modified by body mass index (BMI), including several previously reported potential liver disease therapeutic targets, for example, PNPLA3, HSD17B13, and MARC1 . While further work is necessary to understand the effect of ALT and AST‐associated variants on liver disease, the weighted burden of significant BMI‐modified signals is significantly associated with liver disease outcomes. In summary, this study identifies genetic associations which offer an important step forward in understanding the genetic architecture of serum ALT and AST levels. Significant interactions between BMI and genetic loci not only highlight the important role of adiposity in liver damage but also shed light on the genetic etiology of liver disease in obese individuals.